Crystal Growth of Ceasium Hydrogen Sulfate Salts 4CsHSO - Al-Dhahir, Tariq A.; Al-Harbi, Khalid H.; Al-Zubaidi, Ala’a.A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Single crystal of CsHSO4 component was grown by slow evaporation method of aqueous solution with normality N=1 . The study shows that the importance of the process of Recrystal growth of CsHSO4 crystals. The results show the improve of the characteristics of crystals (transparent, size, shape, number and quality) . By X-Ray diffraction, the crystal structure of these crystals have been confirmed by measurement constants of unit cell of crystal lattice. The vibration modes of crystals were studied by FTIR (Fourier Transform Infrared) technique. Finally, achieving the study of microstructure of crystals by polarization of microscopy that is supported with hot stage at different temperatures. The changes occur on these crystals by changing in positions of atoms and changing in the colors of crystals especially at temperatures near the phase transition were studied.